Basic principles and practice of business administration - Edebe, Ambrose ([Place of publication not identified] : Xlibris, 2013)
The primary purpose of this book is to provide students and others with a concise, thoroughly up-to-date book which will enable them to obtain a sound knowledge of the basic principles and practice of business administration for examination and practical purposes. This book has been produced to make the learning of business administration simple as well as interesting, and intelligent study should equip the reader with a basic knowledge of business administration. This book is a review and study guide. It helps in preparing for exams, in doing homework, and remains a handy reference source at all times. It will thus save hours of study and preparation time. The book provides quick access to the important principles, definitions, strategies, and concepts in business administration. Materials needed for exams can be reviewed in summary form - eliminating the need to read and re-read many pages of textbook and class notes.
Principles of management -- The human resource function -- The purchasing and marketing functions -- The production function -- The administrative function.
Includes bibliographical references.
Keywords: Industrial management; Gestion d'entreprise.; Industrial management